2009
DOI: 10.1007/s00125-009-1380-1
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in the natural progression of nephropathy among diabetes patients in New Zealand: hospital admission rate for renal complications, and incidence of end-stage renal disease and renal death

Abstract: There were huge ethnic disparities in outcomes from renal disease. Screening for early kidney disease among Maori diabetes patients, intensive management of risk factors and further research on the aetiology of renal disease among Maoris is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…In our clinical experience, the Samoan community exhibits a disproportionate rate of kidney and related chronic conditions (such as obesity and diabetes) compared with the general population. This situation is also reported in other parts of Australia (McDonald & Russ, 2003) with large Samoan populations; as well as in New Zealand (Joshy, Dunn, Fisher, & Lawrenson, 2009;Sundhorn et al, 2008;Tomlin, Tilyard, Dawson, & Dovey, 2006) and the United States (Galanis, McGarvey, Quested, Sio, & Afele-Fa'Amuli, 1999;Pearson, 2008). This article demonstrates how a culturally sensitive framework, Fa'afaletui, guided a research project that aimed to increase our understanding of the factors contributing to these issues in one Samoan community in Queensland, Australia, and helped us plan strategies that might ameliorate these issues.…”
Section: Introductionmentioning
confidence: 63%
“…In our clinical experience, the Samoan community exhibits a disproportionate rate of kidney and related chronic conditions (such as obesity and diabetes) compared with the general population. This situation is also reported in other parts of Australia (McDonald & Russ, 2003) with large Samoan populations; as well as in New Zealand (Joshy, Dunn, Fisher, & Lawrenson, 2009;Sundhorn et al, 2008;Tomlin, Tilyard, Dawson, & Dovey, 2006) and the United States (Galanis, McGarvey, Quested, Sio, & Afele-Fa'Amuli, 1999;Pearson, 2008). This article demonstrates how a culturally sensitive framework, Fa'afaletui, guided a research project that aimed to increase our understanding of the factors contributing to these issues in one Samoan community in Queensland, Australia, and helped us plan strategies that might ameliorate these issues.…”
Section: Introductionmentioning
confidence: 63%
“…The rate of progression of diabetic nephropathy will also affect rates of DN‐related RRT. There are no cohort studies directly comparing rates of disease progression between indigenous and non‐indigenous groups in Australasia; however, observational studies suggest that Māori and Pacific people with diabetes are more likely to develop ESKD than other NZ diabetics 28 . Differences in diabetes care, timing of diabetes diagnosis, 29 glycemic control, smoking 30 and obesity 28 might explain much of the differences in incidence of DN between racial groups in NZ.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline median duration of diabetes varied from 0 to 29 years. Two studies [29,47] recruited study participants at the time of diabetes diagnosis, but 13 studies did not report the baseline duration of diabetes [12,13,27,36,40,50,56,57,71,74,77,78,81]. Characteristics of the 71 included studies are presented in Table S1.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…Several studies reported a higher incidence of ESRD among men than women [25,48,51], but others [47,53,64] reported no significant differences. Incidence of ESRD was higher among African Americans [20,27,29], native people in Canada [77] and Maoris in New Zealand [81] compared with white people (Europids). The hazard of ESRD was also reported higher in Latinos, Chinese, Japanese and Pacific Islanders [20].…”
Section: Incidence Of Esrd Among People With Diabetesmentioning
confidence: 99%